Experimental and modelling study of the multichannel thermal dissociations of CH3F and CH2F. Issue 4 (10th January 2018) - Cobos, C. J.; Knight, G.; Sölter, L.; Tellbach, E.; Troe, J.
Abstract : The thermal unimolecular dissociation of CH3 F was studied in shock waves by monitoring the UV absorption of a dissociation product identified as CH2 F. Abstract : The thermal unimolecular dissociation of CH3 F was studied in shock waves by monitoring the UV absorption of a dissociation product identified as CH2 F. It is concluded that, under conditions applied, the formation of this species corresponds to a minor, spin-allowed, dissociation channel of about 3% yield. Near to the low-pressure limit of the reaction, on the other hand, the energetically more favourable dissociation leads to 3 CH2 + HF on a dominant, spin-forbidden, pathway. By considering the multichannel character of the reaction, it is shown that, in contrast to the low-pressure range, the high-pressure range of the reaction should be dominated by CH2 F formation. The channel-switching probably takes place at pressures higher than those applied in the present work. In addition to the two dissociation channels of CH3 F producing 3 CH2 + HF and CH2 F + H, a third, spin-allowed, dissociation channel leading to 1 CHF + H2 was also considered and estimated to proceed with a yield smaller than 0.5%. Besides the dissociation of CH3 F, the dissociation of CH2 F was studied by monitoring the UV spectrum of CH2 F. Details of this spectrum were investigated. Similar to CH3 F, the dissociation of CH2 F can proceed on several dissociation channels, under the present conditions either to CHF + H or to CF + H2 . After modelling single-channel falloff curves for all reaction pathways, coupling effects of multichannel dissociations were interpreted in the framework of multichannel unimolecular rate theory.